Electrochemical Evaluation of Human Hair Derived Carbon Particles. (12th June 2020) - Atif, Muhammad; Farid, Muhammad Qamar; Ahmad, Sheikh Asrar; Abdul Karim, Ramzan; Hussain, Azhar; Rabbani, Faiz; Bongiovanni, Roberta
Abstract : Pollution has become a great challenge for modern world. Hence, recycling trend is growing worldwide. Human hair, a fancy part of human body, creates a bulk of litter on trimming, yet has wide spectrum of applications. A facile thermal approach has been implemented in this research to synthesize carbon particles (CP) from waste human hair. CP surface analyses was made through SEM, ATR-FTIR, TGA & Raman. Efficient adsorptive behavior of synthesized CP against Zn and Pb has been observed with 70% Pb (9.325 mg/10 mg CP) and 90% Zn (37 mg/10 mg CP) adsorption. The augmented adsorptive capacity of CP ultimately finds its application in heavy metal removal from waste water. Cyclic voltammetry (CV) justified outstanding adsorption behavior of CP by speedy electron transfer, better charge storage and swift ionic diffusion; with 53 mC current carrying capacity and 1.98 to 4.37 cm 2 effective surface area. CV data has shown electrochemical irreversibility and double layer capacitance. CP conductivity has been observed from 19.78 μ S to 38.4 μ S, with ζ values between −17.4 mV and −28.6 mV.